Contribution to the taxonomy of the genus Coeleumenes van der Vecht, 1963 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species - Nguyen, Lien Thi Phuong (Zootaxa, 2016)
Coeleumenes flavus sp. nov is described and illustrated from Vietnam (Son La), C. burmanicus van der Vecht, 1963 is redescribed. A key to both species from Vietnam is given.